Circularly Polarized Organic Ultralong Room‐Temperature Phosphorescence with A High Dissymmetry Factor in Chiral Helical Superstructures - Liu, Jiao; Song, Zhen‐Peng; Wei, Juan; Wu, Jun‐Jie; Wang, Meng‐Zhu; Li, Jian‐Gang; Ma, Yun; Li, Bing‐Xiang; Lu, Yan‐Qing; Zhao, Qiang (Advanced materials (Weinheim), 2024)
Long‐lived room‐temperature phosphorescence (RTP) of organic materials holds a significant potential for optical information. Circularly polarized organic ultralong room‐temperature phosphorescence (CP‐OURTP) with extremely high dissymmetry factor (glum) values is even highly demanded and considerably challenging. Here, an effective strategy is introduced to realize CP‐OURTP with an emission decay time of 735 ms and a glum value up to 1.49, which exceeds two orders of magnitude larger than previous records, through a system composed of RTP polymers and chiral helical superstructures. The system exhibits excellent stability under multiple cycles of photoirradiation and thermal treatment, and is further employed for information encryption based on optical multiplexing. The results are anticipated to lay the foundation for the development of CP‐OURTP materials in advanced photonic applications. An effective strategy is presented to realize circularly polarized organic ultralong room‐temperature phosphorescence (CP‐OURTP) with an emission decay time of 735 ms and a glumvalue up to 1.49. The CP‐OURTP materials obtain exhibit excellent stability under multiple cycles of photoirradiation and thermal treatment. Moreover, information encryption based on optical multiplexing using the prepared CP‐OURTP materials is demonstrated.